Efficacy of Multivalent Adenovirus-Based Vaccine against Simian Immunodeficiency Virus Challenge - Casimiro, Danilo R. (American Society for Microbiology (ASM), 2010)
The prophylactic efficacies of several multivalent replication-incompetent adenovirus serotype 5 (Ad5) vaccines were examined in rhesus macaques using an intrarectal high-dose simian immunodeficiency virus SIVmac239 challenge model. Cohorts of Mamu-A*01(+)/B*17(−) Indian rhesus macaques were immunized with one of several combinations of Ad5 vectors expressing Gag, Pol, Nef, and Env gp140; for comparison, a Mamu-A*01(+) cohort was immunized using the Ad5 vector alone. There was no sign of immunological interference between antigens in the immunized animals. In general, expansion of the antigen breadth resulted in more favorable virological outcomes. In particular, the order of efficacy trended as follows: Gag/Pol/Nef/Env ≈ Gag/Pol > Gag ≈ Gag/Pol/Nef > Nef. However, the precision in ranking the vaccines based on the study results may be limited by the cohort size, and as such, may warrant additional testing. The implications of these results in light of the recent discouraging results of the phase IIb study of the trivalent Ad5 HIV-1 vaccine are discussed.